2001
DOI: 10.14411/fp.2001.004
|View full text |Cite
|
Sign up to set email alerts
|

Dendromonocotyle colorni sp. n. (Monogenea: Monocotylidae) from the skin of Himantura uarnak (Dasyatididae) from Israel and a new host record for D. octodiscus from the Bahamas

Abstract: Abstract. Dendromonocotyle colorni sp. n. (Monogenea: Monocotylidae) is described from the dorsal skin surface of two specimens of Himantura uarnak (Forsskål) kept at the Eilat Underwater Observatory in Israel. Dendromonocotyle colorni is distinguished from the other eight species in the genus by the morphology of the terminal papillar sclerite on the haptor, the distal portion of the male copulatory organ and the morphology of the vagina. The development of the male copulatory organ is detailed for D. colorni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…After the cleaning events, no remnants of monogeneans were found in the stomach contents of the cleaner fish, but unidentified specimens of Dendromonocotyle were found on the rostrum, the posterior part of the disc and the base of the tail of the ray. Chisholm et al (2001a) confirmed the identity of these specimens as D. octodiscus and established that dark pigment that may conceal the worms was present in the intestinal caeca. Therefore, it appears that T. bifasciatum may overlook camouflaged D. octodiscus on ray skin.…”
Section: Biology Of Dendromonocotylesupporting
confidence: 62%
See 1 more Smart Citation
“…After the cleaning events, no remnants of monogeneans were found in the stomach contents of the cleaner fish, but unidentified specimens of Dendromonocotyle were found on the rostrum, the posterior part of the disc and the base of the tail of the ray. Chisholm et al (2001a) confirmed the identity of these specimens as D. octodiscus and established that dark pigment that may conceal the worms was present in the intestinal caeca. Therefore, it appears that T. bifasciatum may overlook camouflaged D. octodiscus on ray skin.…”
Section: Biology Of Dendromonocotylesupporting
confidence: 62%
“…The morphology of the male copulatory organ can change considerably as the parasite matures (see Chisholm andWhittington 1995, Chisholm et al 2001a) therefore, it is important to use adult worms to identify species. Detailed terminology and illustrations of taxonomic characters used in the following key to species are provided in , Chisholm et al (2001a) and Chisholm and Whittington (2004) …”
Section: Taxonomy Of Dendromonocotylementioning
confidence: 99%
“…The "spermatophore", seen in the proximal region of the vagina of M. borneoensis, differs morphologically from those observed in the other two Myliocotyle species and from those described in other monocotylids (e.g. Dendromonocotyle species; see Chisholm et al 2001). Accessory sclerites have been observed in the vagina of other monocotylids (e.g.…”
Section: Discussionmentioning
confidence: 58%
“…We are, however, unaware of a penis stylet elsewhere in the class. The stylet of R. kiatkiongi is simple, sharp-ended, and lacking in armature, appearing analogous to the stylets present in some Monogenea and Turbellaria (Chisholm et al 2001). This remarkable feature alone suggests that this form merits a new genus.…”
Section: Discussionmentioning
confidence: 71%